Three-dimensional constitutive model for shape-memory polymers considering temperature-rate dependent behavior. (16th February 2021) - Kim, Jinsu; Jeon, Seung-Yeol; Hong, Seokbin; An, Yongsan; Park, Haedong; Yu, Woong-Ryeol
Abstract: The temperature-rate dependent thermomechanical behavior of shape-memory polymers (SMPs) is challenging to study, because the microstructure of SMPs cannot rearrange instantaneously to an equilibrium configuration in response to temperature changes. Herein, we report a temperature-rate dependent three-dimensional constitutive model for SMPs based on a two-phase model consisting of rubbery and glassy phases. To describe the effect of temperature rate on SMPs, the variation of the volume fraction of each phase affected by temperature was considered under different temperature-rate conditions. Additionally, the temperature-rate dependent thermal strain was incorporated into the two-phase model. The developed constitutive model was validated by simulating the shape-memory behavior of SMPs, and by comparing the simulation and experimental results under different temperature-rate conditions.